Efeito do revenimento sobre a resistência à corrosão do aço inoxidável uns s41426 - Santos, Icaro Gabriel Rodrigues (Universidade Federal de São Carlos, 2020)
Supermartensitic stainless steels were developed during the 1990s as an alternative to duplex stainless steels for manufacture of oil country tubular goods. As a result of microstructural variations caused during tempering process, different corrosion behaviors have been reported for supermartensitic steels, making necessary to deepen the knowledge of microstructural effects in the formation of the passive film and in the corrosion resistance of these materials. The present research aimed to study the impact of the tempering temperature on the corrosion resistance of a UNS S41426 supermartensitic steel. The material was solution treated at 1050 °C during 1 h and quenched in air, lately, tempered at 550, 600, 650, 700 and 650 + 600 °C for 2 h and air cooled. General corrosion was evaluated by immersion tests in 0.5 M H2SO4. The intergranular corrosion resistance and Cr-depletion degree was evaluated by DL-EPR tests in 0.5 M H2SO4 + 0.01 M KSCN. Potentiodynamic polarization in H2SO4 and 3.5% NaCl were used, respectively, to analyze the passive behavior of the material and the pitting resistance. The results shows that the tempering treatments leads to formation of reverse austenite that increases the Cr-depletion degree and the materials intergranular corrosion. In addition, the presence of this phase causes the quickly formation of passive film in lower potentials as result of the Ni enrichment, reducing the generalized corrosion. However, in more oxidizing environments, the passive film formed on the austenite has less protective character. The pitting potentials has no variation accordingly to the studied tempering treatments. Finally, tempering in 650 °C seems to be more adequate to the USN S41426 SMSS.
Tempering effect on corrosion behavior of uns s41426 stainless steel
Keywords: Aço inoxidável supermartensítico; Revenimento; Austenita reversa; Resistência à corrosão; Polarização; Supermartensitic stainless steel; Tempering; Reverse austenite; Corrosion resistance; Polarization; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA